PHYSICAL EDUCATION AT SCHOOL: THE HIGH SCHOOL STUDENT'S CONCEPTION (Fiep Bulletin - online, 2014)
The present article shows the results and reflections taken after the study category that deals with the conception of Physical Education for High School students, from a survey introduced as a Final Paper in the Physical Education Course at FEEVALE in 2005. The goal of the study, in a whole, was to acknowledge and understand the perception of this kind of students on the activities and contents developed in the Physical Education classes. However, for this article, it was taken into consideration only one of the specific goals aiming the students knowledge on the subject and identify aspects that influence this conception. The survey was based on the qualitative, interpretative descriptive pattern with case study. The case study was a private school in Taquara-RS/Brazil. The instruments applied into the data collection were: observations of the classes, semistructured interview with fifteen students, field routine and documentary analysis. Data analysis occurred through triangulation of data. The results show that students have different knowledge on the Physical Education subject that according to tendencies given by Guiraldelli (1989) are: hygienist, competitive and popular. After this, the conclusion is that the idea from those students about the subject is associated to the educational context in which they are inserted and the class reference they have daily.
Keywords: Physical Education; Conception; High School